Differential responsiveness of myc- and ras-transfected cells to growth factors: selective stimulation of myc-transfected cells by epidermal growth factor. - Stern, D F (1986)
To identify functional relationships between oncogenes and growth factors, we compared the effects of transfected myc and ras oncogenes on the responsiveness of Fischer rat 3T3 cells to three growth factors: epidermal growth factor (EGF), platelet-derived growth factor (PDGF), and transforming growth factor-beta (TGF-beta). Control cells did not grow in soft agar under any conditions. ras-Transfected cells grew in soft agar under all conditions tested and were insensitive to the stimulatory effects of exogenous growth factors. These cells secreted elevated levels of both EGF-like factors and TGF-beta, suggesting that the lack of responsiveness of these cells to exogenous growth factors arose from autocrine stimulation. myc-Transfected cells displayed conditional anchorage-independent growth: they formed numerous colonies in soft agar in the presence of EGF but relatively few colonies in the presence of PDGF or TGF-beta. Secretion of EGF-like factors and TGF-beta by these cells was not elevated above that of control cells. These results suggest a model for the mechanism of cooperation between myc and ras oncogenes in which ras-like genes induce growth factor production, while myc-like genes increase the responsiveness of cells to these factors.